Survey of healthcare professionals' knowledge, attitudes and practices regarding spontaneous intracranial hypotension. Issue 2 (5th September 2022) - Cheema, Sanjay; Anderson, Jane; Duncan, Callum; Davagnanam, Indran; Armstrong, Paul; Redfern, Nancy; Ordman, Anthony; D'Antona, Linda; Nissen, Justin; Sayal, Parag; Vaughan-Huxley, Eyston; Lagrata, Susie; et al.
Abstract : Objective: To assess the knowledge, attitudes and practices of healthcare professionals regarding the diagnosis and management of spontaneous intracranial hypotension (SIH). Methods: We performed a cross-sectional, web-based survey of multiple healthcare professional groups in the UK from June to August 2021. There were 227 respondents to the survey, including 62 general practitioners, 39 emergency medicine physicians, 38 neurologists, 35 radiologists, 20 neurosurgeons, 18 anaesthetists and 15 headache nurse specialists. The majority of the respondents were at the consultant level and all worked in the UK National Health Service. Results: Few general practitioners or emergency medicine physicians had ever been involved in the care of a patient with SIH or received teaching about SIH. Only 3 of 62 (4.8%) general practitioners and 1 of 39 (2.5%) emergency medicine physicians were confident in recognising the symptoms of SIH. Most neurologists were confident in recognising SIH and performed MRI of the brain as a first-line investigation, although there was variability in the urgency of the request, whether contrast was given or MRI of the spine organised at the same time. Most said they never or rarely performed lumbar puncture for diagnosis of SIH. Most neuroradiologists, but few general radiologists, were confident in interpreting imaging of patients with suspected SIH. Lack of access to epidural blood patching, personnel able to perform myelography, and established management pathways were identified by many respondents as barriers to the treatment of SIH. Conclusions: We have identified a lack of awareness of SIH among non-specialists, several barriers to optimal treatment of SIH and a variation in current management pathways. The results highlight the need for education of healthcare professionals about SIH and the development of clinical practice guidelines to enable delivery of optimal and equitable care for patients with SIH.